The Effects of Mindfulness on Decreased Insomnia Student - Tri Septiana; Frili Amelia; Alsa Apriani (Journal of Psychology and Social Sciences, 2024)
This study aimed to identify whether Mindfulness training can reduce insomnia-related symptoms. This research discusses sleep pattern disorders, especially insomnia, in students at the Faculty of Ushuluddin and Islamic Thought at UIN Raden Fatah Palembang. Insomnia can affect students' quality of life and well-being, including academic performance and mental health. This research used a quantitative experimental approach involving 20 students from the Faculty of Ushuluddin and Islamic Thought at UIN Raden Fatah Palembang consisting of the experimental group. The research method uses a One-Group Pretest-Posttest Design which involves a pre-test and post-test using the Insomnia Rating Scale as the main measurement instrument. The results of data analysis using the t-test showed significant differences between conditions before and after administering the Mindfulness technique. The T-test test results showed a significant difference between the pretest and post-test. In the Pre-test, the average score for sleep disturbance was 18.90, while in the Post-test, the average score for sleep disturbance was 4.10. Providing Mindfulness techniques during four meetings, each lasting 20 minutes, succeeded in reducing the level of sleep disorders in students.